Fungi-based food in the public eye: Terminology, cultivation timelines, sustainability, and nutrition across three EU countries - Coralie Hellwig; Mohammad J. Taherzadeh (PLoS ONE, 2026)
Fungi-based foods are gaining attention as sustainable alternatives, yet public understanding remains limited. This study quantified knowledge and perceptions in Germany, Spain, and Sweden, selected for their distinct dietary cultures and regulatory contexts. An online survey of 6,004 adults used quiz-style questions covering taxonomy, terminology, cultivation timelines, sustainability, and nutrition. Results show misconceptions. Many classified fungi as plants, were unfamiliar with mycoprotein, and underestimated the rapid cultivation of filamentous fungi. Despite these gaps, majorities in all countries endorsed fungi’s sustainability potential and nutritional parity with meat. Greater knowledge was observed among tertiary-educated, higher-income, and meat-reducing groups. These findings show that limited process-related factual knowledge exists, underscoring the need for clearer communication. Public messaging should employ accessible terminology, present fermentation as ‘grown in days,’ and emphasize nutritional properties. Addressing knowledge gaps can align perceptions with evidence, enable informed decision-making, and support integration of fungi-based foods into sustainable systems.